2015
DOI: 10.1186/s12870-015-0477-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of inflorescence and plant height components in sorghum (Panicoidae) and comparative genetics with rice (Oryzoidae)

Abstract: BackgroundDomestication has played an important role in shaping characteristics of the inflorescence and plant height in cultivated cereals. Taking advantage of meta-analysis of QTLs, phylogenetic analyses in 502 diverse sorghum accessions, GWAS in a sorghum association panel (n = 354) and comparative data, we provide insight into the genetic basis of the domestication traits in sorghum and rice.ResultsWe performed genome-wide association studies (GWAS) on 6 traits related to inflorescence morphology and 6 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 63 publications
(127 reference statements)
17
73
0
Order By: Relevance
“…Dw2 has been mapped to chromosome 6 (Feltus et al, 2006;Zou et al, 2012;Nagaraja Reddy et al, 2013), and its effect on plant height is frequently detected in GWAS as a large genomic region encompassing almost the entire chromosome 6. This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Dw2 has been mapped to chromosome 6 (Feltus et al, 2006;Zou et al, 2012;Nagaraja Reddy et al, 2013), and its effect on plant height is frequently detected in GWAS as a large genomic region encompassing almost the entire chromosome 6. This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016). In spite of the similar performance and efficiency of both algorithms to estimate the actual morphological trait, Auto-PHe has the advantage of being an automatic processing pipeline with reduced run time and concomitant cost.…”
Section: Discussionmentioning
confidence: 94%
“…In sorghum, a few association mapping studies have been performed to investigate specific plant characteristics using a diversity panel (Brown et al, 2008; Shehzad et al, 2009; Murray et al, 2009; Mantilla Perez et al, 2014) and a mini core panel (Upadhyaya et al, 2012a,b) with limited genome coverage. Additionally, several GWAS have been recently conducted using high‐throughput genotyping data to discover the genetic control of grain polyphenol concentration (Rhodes et al, 2014), flavonoid pigmentation traits (Morris et al, 2013b), aluminum tolerance and grain yield in P‐limited environments (Leiser et al, 2014), resistance to stalk rot diseases (Adeyanju et al, 2015), seed size (Zhang et al, 2015b), and plant height and inflorescence trait components (Morris et al, 2013a; Zhang et al, 2015a).…”
mentioning
confidence: 99%
“…Genome-wide association study (GWAS) with SNPs generated by genotyping by sequencing (GBS) has been widely used in all major crops including maize, rice, barley, tomato, wheat, sorghum, soybean, watermelon and several other important plant species1011121314 and found effective for mining new genes; however, the population structure must be resolved accurately to reduce spurious associations because of confounding effects of subpopulations. The current research aims to identify genomic segments linked to various fruit traits and capsaicin accumulation in diverse collections of C. annuum .…”
mentioning
confidence: 99%